Comparison of protein patterns between Plasmodium falciparum mutant clone T9/94-M1-1(b3) induced by pyrimethamine and the original parent clone T9/94 - Rungsihirunrat, Kanchana (Asian Pacific Tropical Medicine Press, 2012)
OBJECTIVE: To compare the protein patterns from the extracts of the mutant clone T9/94-M1-1(b3) induced by pyrimethamine, and the original parent clone T9/94 following separation of parasite extracts by two-dimensional electrophoresis (2-DE). METHODS: Proteins were solubilized and separated according to their charges and sizes. The separated protein spots were then detected by silver staining and analyzed for protein density by the powerful image analysis software. RESULTS: Differentially expressed protein patterns (up- or down-regulation) were separated from the extracts from the two clones. A total of 223 and 134 protein spots were detected from the extracts of T9/94 and T9/94-M1-1(b3) clones, respectively. Marked reduction in density of protein expression was observed with the extract from the mutant (resistant) clone compared with the parent (sensitive) clone. A total of 25 protein spots showed at least two-fold difference in density, some of which exhibited as high as ten-fold difference. CONCLUSIONS: These proteins may be the molecular targets of resistance of Plasmodium falciparum to pyrimethamine. Further study to identify the chemical structures of these proteins by mass spectrometry is required.